"We Always Say: And Then Came The Water…"1 Flint's Emergent Latinx Capacity Building Journey During the Government-Induced Lead Crisis. Issue 3 (2nd October 2017) - Duntley-Matos, Roxanna; Arteaga, Victoria; García, Angel; Arellano, Rafael; Garza, Roberto; Ortega, Robert M.
ABSTRACT: This critically intersubjectively engaged ethnography focuses on incipient Latinx lead crisis rehabilitation efforts in Flint, MI and the role of education in the context of multicultural struggles for validation. We employ the paradigms of cultural humility, transformative complicity, and empowerment with a focus on organizing strategies that honor faith-based, union, and urban gardening histories. New Orleans and El Caño Martín Peña environmental crisis research inform our comparative analysis. Our popular pedagogical methods promote agency with detained youths from Kalamazoo who join Flint coauthors through protest music, testimonies, and commentaries to interweave, support, and disrupt authorial and community leader privilege.